Latent herpes simplex virus type 1 in normal and Alzheimer's disease brains. - Jamieson, G; Maitland, N; Wilcock, G; Craske, J; Itzhaki, R (1991)
A viral aetiology has long been suspected for Alzheimer's disease (AD) but until now, techniques have not been sufficiently sensitive to provide clear evidence for or against the presence of any viral genome in AD brain. We have used the very highly sensitive method of polymerase chain reaction to look for herpes simplex virus type 1 (HSV1) DNA, specifically the viral thymidine kinase (TK) gene, in autopsy brain specimens. DNA-samples from HSV-infected and uninfected Vero cells have been examined concurrently to provide standard "HSV-positive" and "HSV-negative" samples, the latter guarding also against false positives caused by cross-contamination. To preclude false negatives, we have checked the presence of the human gene, hypoxanthine phosphoribosyl transferase. In all specimens from 8 AD patients and 6 normal individuals (temporal, frontal and hippocampal), we have found viral TK sequences. In contrast, in preliminary studies on lymphocytes from normals and AD patients, we did not find TK sequences. It is postulated that factors such as number or expression of viral genes and host susceptibility might be related to incidence of AD.